Pengaruh Jenis Dan Konsentrasi Auksin Terhadap Pertumbuhan Dan Perkembangan Tanaman Anggrek Dendrobium mirbelianum Secara In Vitro - Galensong, Justio P.D.; Tilaar, Wenny; Rogi, Johannes E.X.; Lengkong, Edy F.; Walingkas, Stanley A.F.; Inkiriwang, Annatje E.B. (Sam Ratulangi University, 2024)
This study aims to determine the effect of auxin type and concentration on the growth and development of orchid plants. The research was conducted at the Tissue Culture Biotechnology Laboratory, Faculty of Agriculture, Sam Ratulangi University Manado, and was carried out over 2 months from July to August 2023. This study used a factorial experiment in a Completely Randomized Design (CRD) with 5 replications consisting of two factors. The first factor is the type of auxin: IAA (A1), NAA (A2), and IBA (A3), and the second factor is the concentration of each auxin: 1 ml/l (K1), 2 ml/l (K2), and 3 ml/l (K3). The data were analyzed using analysis of variance, and if the results were significant, a 5% Least Significant Difference (LSD) test was conducted. The results showed that there was an interaction between the type and concentration of auxin on variables such as the number of roots, root length, root emergence time, number of leaves, number of shoots, and shoot height. Similarly, there was an effect of auxin concentration on each type of auxin, but there was a significant effect of individual auxin types (IAA, NAA, and IBA) on the root formation of Dendrobium mirbelianum orchids, affecting variables such as the number of roots, root length, root emergence time, number of leaves, number of shoots, and shoot height.